Internalizing character education through javanese traditional dance to realize child-friendly school - Supeni, Siti; Harini, Setyasih (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
The aims of the research are to (1) identify character education in various Javanese traditional dance, (2) to analyze the needs, output, problems, and learning objectives of child-friendly schools (CFS) in implementing character education based on regional dance, and (3) to identify types of Javanese traditional dance values. The methods of collecting the data used literary studies, interviews, surveys, observations, and documentation. In analyzing the data, the researchers employed Research & Development model. Model of regional cultural development based on character education is supported through a psychological, educative, and socio-cultural approach, with qualitative descriptive analysis implemented in 2020. The research findings show that (1) identification character education in various Javanese traditional dance, (2) the needs, output, problems, and learning objectives of child-friendly schools (CFS) in implementing character education based on regional dance, and (3) types of Javanese traditional dance values. The implication of the research is the implementation of character education for elementary school students.